Genetic Inheritance Risk Calculation as a Practical Approach in Health Prevention and Management: A Perspective - Henri Setiawan; Suhanda Suhanda (Inspirasi Foundation, 2024)
In the genomic era, understanding the risk of inheriting genetic diseases has become a crucial element in designing effective health prevention and management strategies. The initial step in calculating the risk of genetic inheritance involves gathering information about family health history. Through the analysis of genetic data and family health history, healthcare professionals can determine an individual's potential genetic risk for various diseases. Calculating the risk of genetic inheritance has several important benefits, including early prevention and management, family planning, genetic counseling, targeted therapy and care development, and informed medical decision making. By knowing an individual's genetic risk for a particular disease, they can take appropriate prevention measures or early management actions. These may include lifestyle changes, regular health check-ups, or even advanced genetic testing for early detection. In Family Planning, calculating genetic risk can assist individuals and couples in planning pregnancies and families more effectively. If a high risk is detected, couples can consider options such as genetic counseling, premarital screening, or selecting suitable reproductive methods. Overall, calculating the risk of inheriting genetic diseases can provide individuals and families with valuable information to take preventive measures, make informed medical decisions, and manage their health more effectively.